PERFORMANCE OF BROILER FED ON VEGETABLE WASTES SUPPLEMETED DIETS* (Indian Journal of Animal Production and Management, 2014)
An experiment was conducted for six weeks with two hundred forty day-old commercial broiler chicks of uniform body weight to study the growth performance fed on vegetable wastes supplemented diets. The chicks were divided randomly in to four experimental groups, viz. C, T1, T2 and T3 consisting of 60 chicks in each group. The control diet was prepared by using conventional feed ingredients. The starter and finisher diets for T1, T2 and T3 groups were prepared by supplementing the control diet with 50 per cent cabbage waste meal, 50 per cent cauliflower waste meal, and 50 per cent mixed (1:1) cabbage and cauliflower waste meal respectively. The mean body weight of birds were found to be 1722.33 ± 12.86, 1642.30 ± 19.54, 1644.33 ± 6.43 and 1584.33 ± 6.38 g for C, T1, T2 and T3 groups respectively. The average body weight gain of birds was found to be higher (P
Keywords: Broiler; Vegetable wastes; cost of feeding